Temperature dependence of dielectric properties for Ba(Zr0.25Ti0.75)O-3 thin films obtained from the soft chemical method - Marques, L. G. A.; Cavalcante, L. S.; Simoes, A. Z.; Pontes, F. M.; Santos-Junior, L. S.; Santos, M. R. M. C.; Rosa, I. L. V.; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Elsevier B.V., 2007)
Ba(Zr0.25Ti0.75)O-3(BZT) thin films prepared by the polymeric precursor method (PPM) were annealed at 500, 600, and 700 degrees C for 4h. All films crystallized in the perovskite structure present a crack-free microstructure. Dielectric properties of the BZT thin films were investigated as a function of frequency and applied voltage. The dielectric constant of the films were 36, 152 and 145 at 1 kHz, while the dielectric loss were 0.08, 0.08, and 0.12 at 1 MHz. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: dielectric properties; BZT; thin films; temperature dependence